Involving Young People in Polish and Lithuanian Social Enterprises by Fostering Entrepreneurial Skills and Abil-ities as Entrepreneurial Opportunity at University - Jolita Greblikaite; Włodzimierz Sroka; Neringa Gerulaitiene (Entrepreneurial Business and Economics Review, 2016)
Objective: The paper aims to analyse theoretically and empirically the development of social entrepreneurship in Poland and Lithuania, emphasizing the development of appropriate skills and abilities gained at university as entrepreneurial opportunity.